Konstruksi Nilai-Nilai Perempuan Metropolis Indonesia Dalam Majalah Femina - Dian Swandayani; Nuning Catur Sri Wilujeng (Jurnal Pendidikan dan Kebudayaan, 2010)
The subject of this research is rubric of â€œWaktu Senggangâ€ or Leisure Time in Femina magazine in 2007. The objectives of the research are revealing all kinds of films, music, books which bend the values of metropolis womenâ€™s images and social constructs. Data collecting is conducted through intensive lecture, reading documentation, then categorizing the data. The data, then, analyzed in qualitative descriptive method. The result of the research shows that: 1) the films issued and reviewed in the rubric of â€œWaktu Senggangâ€ in Femina magazine in 2007 are dominated by Hollywood movies; 2) the music genre in the same rubric are mostly pop music with male leading vocal; 3) the books that dominate the rubric are novel or memoir/ biography, which women as the principle character and their problems. The choice on the genre of show, music album, and the reader books reflects an especial female society, which is the metropolis women whom the trend setter is American metropolis women. The choice is not only to determine the self-image of Femina as a female magazine but also to construct a social form that create the taste or the image of the readers as to be the metropolis women, who are different from uneducated country women.